Photocatalytic Degradation of Methylene Blue Using TiO2-Natural Zeolite as A Photocatalyst - Sri Wardhani; Moh. Farid Rahman; Danar Purwonugroho; Rachmat Triandi Tjahjanto; Christiana Adi Damayanti; Ika Oktavia Wulandari (Chemistry Department, The University of Brawijaya, 2016)
TiO2 - zeolite photocatalyst has been prepared by impregnation of TiO2 onto acid -activated natural zeolite. The XRD data confirmed that natural zeolite used in this work is predominated with mordenite and clinoplitolite types, whereas anatase type can be attributed to TiO2. The highest performance of TiO2 – zeolite, which is indicated by surface area of 13.304 m2/g and band gap energy of 3.15 eV, is obtained when 10 mmol of TiO2 is impregnated onto the zeolite. The ability of this photocatalyst is evaluated by examining degradation of methylene blue (MB) in the presence of UV source. The effects of MB concentration, pH and UV irradiation time on the degradation are studied in a batch reactor. It is interesting since the addition of H2O2 can improve the degradation effeciency of MB. The optimum result is achieved at pH 11, duration of UV irradiation of 50 min, showing degradation amount of 98.25 %. Surprisingly, the chemical oxygen demand (COD) in the degraded MB aqueous solution can be reduced about 77.9%, exhibiting the improvement of water quality. No loss of the activity of the degradation efficiency after reusability of this TiO2 - zeolite photocatalyst for at least 4 times.